Workers Layoffs Caused from the COVID-19 Pandemic in Indonesia and the European Union - Al-Fatih, Sholahuddin; Nur, Asrul Ibrahim; Nilasari, Nilasari (University of Jember, Indonesia, 2023)
This article aims to find legal efforts of workers who layoffs caused by COVID-19 pandemic. Layoff in a company can occur when a company goes bankrupt until it cannot meet its employees' salaries. In addition, some others are not affected by layoffs but are laid off without getting a salary. That were a big problem to face new normal era, a daily life after pandemic. Using the normative legal research method, this paper aimed to explain and describe how COVID-19 affected a thousand workers around Indonesia and European Unian. Human rights, especially the rights of worker, use as a tool to analyze, how COVID-19 pandemic affected workers in Indonesia and European Union. As a result, this paper found that many people were laid off because of the COVID-19 pandemic; the government provides some facilities to help people who laid off during and after pandemic COVID-19, both in Indonesia and European Union perspective. Indonesia adopted some program, such as; a) Program for Family Hope; b) Food Donation Without Cash; c) Bantuan Sosial/Bansos; d) Village Funds; e) The Ministry of Social's social charity; f) Pre-Work Card (Kartu Prakerja); g) Donations made by the provincial government; h) Generosity from the city or regency administration; and i) The provincial government offers assistance to those who require housing. While, The EU has a constitution that guarantees that all citizens can work throughout the territory of the member states.